Interoceptive Accuracy Did Not Affect Moral Decision-Making, but Affect Regret Rating for One’s Moral Choices - Tamura, Kaho; Kobayashi, Yoshinari; Ohira, Hideki (Frontiers in Psychology, 2022)
Previous studies have revealed the effect of interoceptive accuracy (IAcc), a behavioral measure of the ability to feel physiological states and regulation for that, which origin emotion on decision-making such as gambling. Given that decision-making in moral dilemma situations is affected by emotion, it seems that IAcc also affects moral decision-making. The present study preliminarily investigates whether IAcc affects decision-making and emotional ratings such as regret for one’s own choices in moral dilemma situations. IAcc did not affect moral choice (deontological or utilitarian option), but affected regret ratings for one’s moral choice in portions of dilemma scenarios. Moreover, people with higher IAcc make deontological choices more rapidly than those with lower IAcc in self-related dilemma scenarios. These results suggest that people with higher IAcc feel stronger emotional conflicts about utilitarian choices but weaker conflicts about deontological choices than people with lower IAcc depending on the moral dilemma scenario.